(untitled) (Medical Forum Monthly, 2024)
Objective: Comparing the efficacy of oral ivermectin with topical permethrin in treating scabies. Study Design: Randomized control trial study. Place and Duration of Study: This study was conducted at the Department of Dermatology, Nishtar Hospital Multan from May 2016 to January 2017. Materials and Methods: One hundred and forty (140) patients were selected for the study. SPSS version 20 was used to analyze the data. Categorical variables presented as frequencies and percentages and numerical variables presented as mean ± standard deviation. Results: A total of One hundred and forty 140 (100%) patients of scabies disease were included in this study in which 101 (72.1%) were male and 39 (27.9%) were female. Mean of patients in group A (permethrin) was 30.65 ± 6.47 and in group B was 29.85 ± 6.59. It was observed that in Group A49 (70%) patients were cured and in Group B 47 (67.1%) patients were cured. When we applied chi-square test to check the association, it was observed that cure was associated with severity of itching for both the groups and not associated with Nocturnal pruritus. Conclusion: It was concluded that for 7 days treatment (Permethrin) had better outcomes and for 14 days treatment, Group B (Ivermectin) had better outcomes.